Emergence from the Shadow: First Peoples' Photographic Perspectives - Thomas, Jeff (The Cultural Work of Photography in Canada, 2011)
Résumé livre : The Cultural Work of Photography in Canada is an in-depth study on the use of photographic imagery in Canada from the late nineteenth century to the present. This volume of fourteen essays provides a thought-provoking discussion of the role photography has played in representing Canadian identities. In essays that draw on a diversity of photographic forms, from the snapshot and advertising image to works of photographic art, contributors present a variety of critical approaches to photography studies, examining themes ranging from photography's part in the formation of the geographic imaginary to Aboriginal self-identity and notions of citizenship. The volume explores the work of photographs as tools of self and collective expression while rejecting any claim to a definitive, singular t... Source: Publisher
OCLC: 966299857
Keywords: _Nettoyé